STRATEGI ADAPTASI HOTEL PARAMA SU DALAM MENINGKATKAN OKUPANSI PADA MASA PANDEMI COVID-19 - Wayan Pandi; Irmayanti Diah Jatiningsih; Edy Semara Putra (STAH Dharma Sentana Sulawesi Tengah, 2022)
ABSTRACTThis research is located in Palu City, namely Parama Su Hotel. The purpose of this study was to determine the adaptation strategy of Parama Su Hotel in increasing occupancy during the Covid19 pandemic. The decline in occupancy resulting from the global Covid-19 pandemic has had a negative impact on the tourism industry, which includes the tourist accommodation or hospitality sector. The hotel sector was paralyzed for several months at the beginning of the spread of the Covid-19 pandemic in Indonesia, that in March 2020. This study used a qualitative approach and analyzed descriptively. Data collection techniques consist of observation, interviews, and documentation. sources of information in this study managers and employees of Hotel Parama Su. Data collection techniques using data analysis techniques Miles and Huberman, namely, data reduction, data presentation, and drawing conclusions. The results showed that the implementation of government regulations in anticipating Covid-19 had a negative impact on the Parama Su hotel. In the worst situation, the hotel tries to survive during the Covid-19 pandemic by managing and controlling the implementation of activities at the Parama Su Hotel.